Key themes for the study of Islam / edited by Jamal J. Elias - "Elias, Jamal J. (ed.)" (Oxford, 2010)
"Key Themes for the Study of Islam" examines the central themes and concepts indispensable to an informed understanding of Islamic religion and society. From Gender and History to Prayer and Prophecy, each authoritative chapter focuses on a single aspect of the religion and presents a critical discussion written by a world expert in that field. Exposing as false the idea that Islam and Muslims are incomprehensible to Western culture, this book will become the first choice for students and experts in religion from disparate fields, who wish to know how Islam relates to vital concepts in religion and society today.
Keywords: Islam